A service-learning educational approach developed the transversal competencies of undergraduate students in an outreach workshop aimed to high school students - Zamorano-González, Pablo; Alausti, Ana; Gago-Calderón, Belén; García-Durán, Laura (My University, 2023)
In the last decade, research institutes and universities have strengthened the development of outreach activities in the biomedical field, involving researchers and professors as well as graduate students, but with little or no implication of undergraduate students. The development of this type of activities, using the Service-Learning educational approach, could be a valuable tool that would manage the acquisition of learning competencies by undergraduate students of Health Science Degrees and would put science at the service of society.In this project, we present the development of the workshop entitled “Exploring the human body”, in which 205 students in their first and second year of a Degree in Nursing or Medicine (University of Málaga, Spain) acted as mentors of 753 high school students (15 to 16 years old) in several school years (since 2016-2017, excluding 2019-2020 and 2020-2021 due to the COVID-19 pandemic). The workshop consisted of five work stations. Each station featured a set of different experiments and activities that were designed to teach the multiple levels by which the human body, and particularly the nervous system, can be studied: biomolecules, cells, tissues, organs and systems. Both high school and undergraduate students gave an evaluation of the workshop via questionnaires (Likert scale-based and short-answer questions) and a debriefing with the university professors. Data showed an overall score of 4.6 Out of 5 points for the workshop by both high school and undergraduate students. In addition, undergraduate students pointed out that their participation had a positive impact on their academic background (4.8 Out of 5 points), mainly due to the improvement of their oral communication skills (78 students) and self-confidence (58 students). Therefore, these results suggest that this methodology would be valid and applicable to develop the transversal competences of the students in Bachelor's degrees of Health Sciences.
Keywords: Enseñanza - Innovaciones; Biomedicina - Estudio y enseñanza - Métodos activos; Estudiantes universitarios; Service-learning methodology; Outreach; Undergraduate students; Workshop; Transversal competencies